Development of composite cereal flour noodles and their technological, antioxidant and sensory characterization during storage - Sajad Ahmad Mir; Zahida Naseem; Shoib Mohmad Wani (Food Chemistry Advances, 2024)
Cereals and their products form an intrinsic part of the human diet, besides contributing to the major portion of dietary energy and nutrients of people worldwide. In this study, composite noodles were prepared by combining different cereal flours (rice, corn and wheat) in order to develop a nutritional and quality product. Five formulations used for the noodle formation were wheat 100 % (W) as control, rice:wheat 50:50 (RW), wheat:corn 50:50 (WC) rice:corn 50:50 (RC) and rice:wheat:corn 34:33:33 (RWC). The samples were evaluated for the different physicochemical, antioxidant, textural, structural, color and rheological parameters during the 40-day storage period. Among the composite flours, the highest protein 9.98%, was found in wheat:corn 50:50 (WC), while the lowest protein content, 7.97 %, was found in rice:corn 50:50 (RC). The visco-elastic behavior of wheat:corn 50:50 (WC) was slightly greater than that of rice:wheat 50:50 (RW) composite flour. The highest DPPH scavenging activity (24.66 %) was found in wheat:corn 50:50 (WC) noodles, while wheat 100 % (W) noodles showed the lowest DPPH scavenging activity (15.23 %). The visco-elastic behavior of wheat:corn 50:50 (WC) was slightly greater than that of rice:wheat 50:50 (RW) composite flour. Also, wheat:corn 50:50 (WC) showed the highest acceptance and rice:corn 50:50 (RC) noodles showed the lowest level of acceptance. The wheat:corn 50:50 (WC), maintained better overall quality attributes as compared to other noodles throughout the storage.